Electro-graphitization and exfoliation of graphene on carbon nanofibers. (June 2017) - Wang, B.; Wolfe, D.E.; Terrones, M.; Haque, M.A.; Ganguly, S.; Roy, A.K.
Abstract: We present electrical current assisted graphitization as an alternative to conventional high temperature annealing of carbon nanofibers. In-situ experiments were performed on individual vapor grown carbon nanofibers inside a transmission electron microscope to measure the changes in resistance as a function of current density while observing the microstructural changes in real time. About 1000 times decrease in resistivity was measured at current density below 10 6  A/cm 2 . Further increase in current density leads to the uniform exfoliation of mostly bi-layer graphene flakes from the skin of the graphitic nanofibers, which leads to further reduction of the electrical resistance. The uniformity of the graphene flake growth over the nanofiber surface area achieved in this study is difficult to achieve with conventional approaches. Further experiments on networked nanofibers suggest that the graphene can remarkably reduce the electrical Kapitza resistance of the nanofiber junctions. The demonstrated processing of such hierarchical nanostructured fibers lead to high surface area and high conductivity carbon nanofibers that can impact flexible electrodes in electrochemical energy conversion or high specific strength composites applications. Graphical abstract: